Influencia del uso combinado de micorrizas (Glomus Sp) y roca fosfórica sobre la productividad del cultivo de maní (Arachis Hipogaea L.) - Loor Vélez, Vicente Ramón (2017)
The present investigation was carried out in the Teaching, Research and Ecological Linkage Unit of the Polytechnic School of Agriculture of Manabí, Manuel Félix López during the months of September 2015 to March 2016, with the purpose of studying the influence of the combined use of mycorrhizae (Glomus sp) and phosphoric rock on the productivity of peanut cultivation of the variety INIAP-381 ROSITA; The factors under study were: mycorrhizal doses (150, 250 and 350 g / ha) and doses of phosphorus (34, 44 and 54 kg/ha). A completely randomized block design was used with four replicates and nine combined treatments and three control treatments in a factorial arrangement (AxB + 3). For the statistical analysis, the variables in which dont know determined statistical difference were submitted to Tukey's test of averages of the 0.05% probability of error, The economic analysis showed that the best marginal rate of return was obtained by treatment in which it was applied only mycorrhiza (250 g/ha) with 29.23%, therefore a favorable net benefit was obtained due to the variation of the Costs. Regarding the variables evaluated, there were no statistically significant differences between the treatments, it was concludes that there was no influence on the application and combined dosage of mycorrhizae and phosphate rock, however, the treatment with application phosphoric rock (44 kg/ha), presented the best average production of 1208.75 kg / ha.